Features of the seasonal succession of phytoplankton in the Crimean coastal area (Black Sea) in years with different climatic conditions (2009–2014) - Bryantseva, Yu.V. (M.G. Kholodny Institute of Botany, NAS of Ukraine, 2021)
Under conditions of climatic changes, it is of great interest to study the dynamics of various functional complexes of phytoplankton species. The long-term influence of previous cold winters on the course of the seasonal succession of phytoplankton, as well as the intensity of blooms in the open waters of the Black Sea, were shown earlier. In the coastal zone, this relationship has not yet been sufficiently studied. Based on regular monitoring studies in the coastal area of Sevastopol from 2009–2014, features of the course of seasonal succession of phytoplankton in years with different climatic conditions were revealed: the “cold” years differed from the “warm” ones by a longer dominance of diatom complexes in terms of cell abundance, especially of small-celled species, which characterize the initial stage of seasonal succession of phytoplankton. The level of development of both diatoms and dinoflagellates was minimal compared to other years, with a shift in the periods of maxima to later months. In contrast, the "warm" years were characterized by the predominance of dinoflagellates for most of the study period, with a shift in timing of the maxima to earlier months. Both diatoms and dinoflagellates reached their maximal development in “warm” years in spring and autumn. In the “moderate” years, phytoplankton development proceeded either by analogy with the “cold” (2009) or “warm” (2011) years. The seasonal succession described above is typical for the northwestern Black Sea, in particular, the Sevastopol coastal area, and differs from the average pattern for the northwestern part described earlier for 1992–1993. The difference consisted of an increase in the proportion of stages I and III due to a decrease in stage II compared to 1992–1993.